The DNA of Enterprise: Jane Jacobs and Henry George on Innovation and Development Through Spin‐Offs. (May 2015) - Ellerman, David
Abstract The main training grounds for entrepreneurial, technical, and business capacities are existing businesses. There are two ways that this training can lead to new growth—just as there are two ways that existing biological DNA can lead to the growth of bio‐mass, namely, (1) existing organisms getting bigger or (2) by spinning out offspring who in turn can spin out more offspring. Where growth has been vibrant, e.g., Silicon Valley, it has followed the second route, growth by offspring. This is also the biological principle of plenitude. Conventional ownership structures lessen the incentives for spin‐offs since managers do not want to reduce the "empire" under their control. The biological principle of plenitude is best implemented with employee‐owned or cooperative firms (e.g., as in the Mondragon cooperative group). Inspired by ideas first proposed by Henry George and Jane Jacobs, this article explores the social benefits of applying the biological principle of plenitude by encouraging the proliferation of enterprises. This poses a conundrum for societies organized around the private business model: How can the social benefits of spin‐offs be realized when managers do not have an incentive to foster new businesses? We conclude with ways to address this problem.